Action Mechanisms of Transcranial Direct Current Stimulation in Alzheimer’s Disease and Memory Loss - Hansen, Niels (Frontiers in Psychiatry, 2012)
The pharmacological treatment of Alzheimer´s disease (AD) is often limited and accompanied by drug side effects. Thus alternative therapeutic strategies such as non-invasive brain stimulation are needed. Few studies have demonstrated that transcranial direct current stimulation (tDCS), a method of neuromodulation with consecutive robust excitability changes within the stimulated cortex area, is beneficial in AD. There is also evidence that tDCS enhances memory function in cognitive rehabilitation in depressive patients, Parkinson´s disease and stroke. TDCS improves working and visual recognition memory in humans and object-recognition learning in the elderly. Neurobiological mechanisms of AD comprise changes in neuronal activity and the cerebral blood flow caused by altered microvasculature, synaptic dysregulation from ß-amyloid peptide accumulation, altered neuromodulation by degeneration of modulatory amine transmitter systems, altered brain oscillations, and changes in network connectivity. tDCS alters (i) neuronal activity and (ii) human cerebral blood flow, (iii) has synaptic and non-synaptic after-effects (iv), can modify neurotransmitters polarity-dependently, (v) and alter oscillatory brain activity and (vi) functional connectivity patterns in the brain. It thus is reasonable to use tDCS as a therapeutic instrument in AD as it improves cognitive function in manner based on a disease mechanism. Moreover, it might prove valuable in other types of dementia. Future large-scale clinical and mechanism-oriented studies may enable to identify its therapeutic validity in other types of demential disorders.